The village chronotope in the artistic world of neorealism (on the material of the writers of Lanka) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article deals with such characteristics of rural chronotope as agriculture, patriarchal character, religiousness, naturalness. The research establishes two forms of rural chronotope realization in neo-realist texts. In the first one – the rural space is combined with historical household time and and this chronotope shows decline of traditional values (agriculture, patriarchal character) therefore it is marked by catas-trophism. The second form of rural chronotopeis created by household time and con-centration on a concept of naturalness.
Keywords: rural chronotope; agriculture; patriarchal character; religiousness; naturalness